High-Efficiency Transformation of Rhizobium leguminosarum by Electroporation - Garg, Bindu (American Society for Microbiology, 1999)
Electrotransformation of Rhizobium leguminosarum was successfully carried out with a 15.1-kb plasmid, pMP154 (Cm(r)), containing a nodABC-lacZ fusion by electroporation. The maximum transformation efficiency, 10(8) transformants/μg of DNA, was achieved at a field strength of 14 kV/cm with a pulse of 7.3 ms (186 Ω). The number of transformants was found to increase with increasing cell density, with no sign of saturation. In relation to DNA dosage, the maximum transformation efficiency (5.8 × 10(8) transformants/μg of DNA) was obtained with 0.5 μg of DNA/ml of cell suspension, and a further increase in the DNA concentration resulted in a decline in transformation efficiency.